ChemInform Abstract: Controlling Chemoselective Transformations of 4‐Acylpyridines via a Pd—C Catalytic Hydrodechlorination—Hydrogenation. Issue 29 (22nd July 2014) - Cheng, Chuanjie; Wang, Bo; Liu, Nan; Chen, Wenwen; Wang, Xinyan; Hu, Yuefei
Abstract The title multi‐step one‐pot reaction affords 4‐alkanoyl‐ and 4‐benzoylpiperidines hydrochlorides, which are isolated by simple filtration.